Rumi's riddle - Schrefer, Eliot, 1978- (Schrefer, Eliot, 1978- Lost rainforest, 2020)
Rumi and his shadowwalker friends, Auriel, Banu, and Gogi must save Caldera from the rumblings of a volcano located beneath the rainforest.